The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.physa.2011.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Random field effects on the phase diagrams of spin-1/2 Ising model on a honeycomb lattice

Abstract: Ising model with quenched random magnetic fields is examined for single Gaussian, bimodal and double Gaussian random field distributions by introducing an effective field approximation that takes into account the correlations between different spins that emerge when expanding the identities. Random field distribution shape dependence of the phase diagrams, magnetization and internal energy is investigated for a honeycomb lattice with a coordination number q = 3. The conditions for the occurrence of reentrant b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…where Q 12 = 1 2 tanh(2βJ) from relations (13), (14), (15), (16), so that for the respective critical point we get 2Q c 12 = 1 or tanh(2β c J) = 1 which implies that…”
Section: Model and Formalismmentioning
confidence: 98%
See 2 more Smart Citations
“…where Q 12 = 1 2 tanh(2βJ) from relations (13), (14), (15), (16), so that for the respective critical point we get 2Q c 12 = 1 or tanh(2β c J) = 1 which implies that…”
Section: Model and Formalismmentioning
confidence: 98%
“…where G k = 3g k0 + 4g k1 + g k2 and the g's functions are defined in (14). The resulting equation for the equilibrium magnetization from ( 9) is…”
Section: Model and Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Blume-Capel (BC) model was created [1,2] , the magnetothermal properties and phase transition properties of BC models on various lattices have been studied [3][4][5] . Canko's scientific research team explored the phase transition characteristics of single-spin [6] (S=1) system, mixed-spin system [7][8] (S=1/2 and S=1, S=1/2 and S=3/2), and found that the lattice field significantly affected the magnetothermal properties and phase transition of the system, especially the negative crystal field.…”
Section: Introductionmentioning
confidence: 99%
“…A problem associated with the ferromagnetic model in a random field is the survival of the tricritical point [10][11][12][13][14]. Depending on the choice of the random-field distribution, for example when it is given by a symmetric double-delta functions [15], the mean-field approximation gives rise to a tricritical point.…”
Section: Introductionmentioning
confidence: 99%